Effect of Different Types of Middle Columns on the Seismic Performance of Single-Story Subway Station Structure - Sheng Li; Haiyang Zhuang; Wei Wang; Liguo Jin; Zhengfang Dong (Shock and Vibration)
In view of the seismic weak component of the single-frame-type subway station structure, the three-dimensional (3D) time-domain nonlinear finite element static-dynamic coupling analysis model of interaction between soil and subway station structure is established by, respectively, using rectangular reinforced concrete (RRC) columns, circular reinforced concrete (CRC) columns, and prefabricated concrete-filled steel tube (CFST) columns with a quick-connection device proposed in this article. This analysis model is further used to investigate the influence of different types of middle columns on the seismic response characteristics of the underground structure, such as the interstory displacement angle, seismic damage, and dynamic response. The results show that, compared with the rectangular columns, the circular columns with the equal moment of inertia suffer less damage in the earthquake and have better seismic performance. The prefabricated CFST columns can effectively ensure that the middle columns of the station structure are not severely damaged and can be replaced quickly after the earthquake, which improves the overall seismic performance of the subway station structure and the rapid recovery ability of the structural function after the earthquake.